HIGHER STUDENTS’ ABILITY IN WRITING NARRATIVE TEXT ON THEIR BLOG - Nurlaela (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Tompotika Luwuk, 2021)
The aim of this study was describing higher students’ ability in writing narration text on their blog. This study method is descriptive quantitative. The data was collected from the 30 higher students in mathematic department of education faculty in Universitas Tompotika Luwuk by asking them to write narration text on their blog. The students were asked to write narration text on their blog that they had chosen. In analyzing the data, I focus on ideas, richness of content, rhetorical features, organization, language control, and mechanism. From the data analyzed, it found that the students’ ability is 399,31 or 66,55% which is classified as high category. From the data calculation, I found that the students’ writing components are as follow: ideas is 98 or 65,33%, richness of content is 86 or 57,33%, rhetorical features is 121 or 80,66%, organization is 90 or 60%, language control is 83 or 55,33%, and mechanism is 121 or 80,66%. This study result implicates as contribution for the lecture, teacher, and students in teaching and learning narration text